Implementasi Sikat Gigi Alarm Dan Vitamin Gigi Secara Mandiri di Sekolah Dasar Wilayah Kecamatan Banyumanik - Salikun Salikun; Sulur Joyo Sukendro; Nanang Qosim (Poltekkes Kemenkes Semarang, 2023)
Dental health is very important aspect, especially in children. The risk of dental disease in children can cause eating disorders and reduced nutritional intake resulting in decreased body weight and suboptimal child growth and development. According to National Basic Health Research, the prevalence of cavities in early childhood is very high, namely 93%, meaning that only 7% of Indonesian children are free from dental caries In 2030. To support government programs, it is necessary to carry out promotive and preventive activities, namely by carrying out Community Partnership Program activities by teaching elementary school children how to brush their teeth properly and correctly by making a toothbrush alarm device providing benefits to help students brush their teeth properly in time, namely after breakfast and at night before going to bed and applying dental vitamins. Brushing teeth is a daily activity that is carried out to be able to maintain healthy teeth. Maintaining good and correct tooth brushing behavior can help reduce the risk of caries. The method of implementing this activity is the use of tooth brushing alarms and the implementation of dental vitamins. Management of children by providing dental health education and dental examinations. From this activity parents and teachers gave a positive response proposing MOU cooperation for this partnership activity. For schools, it is hoped that by establishing cooperation through the signing ofÂ MOU so that the continuation of this promotive and preventive dental health program can run and will ultimately be beneficial in shaping behavior to maintain better dental health.Â Key words : toothbrush alarm; dental vitamins; children